Chemical Characterization and Bioactivity of Extracts from Thymus mastichina: A Thymus with a Distinct Salvianolic Acid Composition - Meriem Taghouti; Carlos Martins-Gomes; Judith Schäfer; João A. Santos; Mirko Bunzel; Fernando M. Nunes; Amélia M Silva (MDPI AG, 2019)
Thymus mastichina, also called mastic thyme or Spanish marjoram, is endemic to the Iberian Peninsula, where it is widely used in folk medicine especially for treating digestive and respiratory systems disorders, and as a condiment to season olives. This work describes for the first time the detailed phenolic composition of exhaustive hydroethanolic extracts and aqueous decoctions of Thymus mastichina. Unlike other species of the Thymus genera, Thymus mastichina extracts contain high amounts of salvianolic acid derivatives, with salvianolic acid A isomer being the main derivative. This isomer was identified in extracts from Thymus mastichina for the first time. Also, an undescribed salvianolic acid derivative in Thymus mastichina was identified and its structure was tentatively described. Extracts from Thymus mastichina showed significant scavenging activity of 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical cation, hydroxyl, and nitric oxide radicals. The anti-proliferative effect of both T. mastichina extracts were tested against Caco-2 and HepG2 cells; the hydroethanolic extract showed a high anti-proliferative activity against Caco-2 cells compared to HepG2 cells (at 24 h exposure, the concentration that inhibits 50% of proliferation, IC50, was 71.18 ± 1.05 µg/mL and 264.60 ± 11.78 µg/mL for Caco-2 and HepG2, respectively). Thus, these results make this species a promising candidate for further investigation of its anti-tumoral potential. Therefore, Thymus mastichina can be potentially used as a functional food (used as a decoction or herbal tea) or as a source of bioactive ingredients with antioxidant and anti-proliferative properties.